Thea at sixteen - Pfeffer, Susan Beth, 1948- (New York : Bantam Books, 1988)
As she seeks her niche in life, Thea becomes involved in volunteer work at the local hospital.
"A Bantam starfire book"--Jacket.
7-10.
Keywords: Sisters -- Fiction; Sisters -- Fiction